Short-term androgen deprivation therapy combined with radiotherapy as salvage treatment after radical prostatectomy for prostate cancer (GETUG-AFU 16): a 112-month follow-up of a phase 3, randomised trial. Issue 12 (December 2019) - Carrie, Christian; Magné, Nicolas; Burban-Provost, Patricia; Sargos, Paul; Latorzeff, Igor; Lagrange, Jean-Léon; Supiot, Stéphane; Belkacemi, Yazid; Peiffert, Didier; Allouache, Nedla; Dubray, Bernard M; Servagi-Vernat, Stéphanie; et al.
Summary: Background: Radiotherapy is the standard salvage treatment after radical prostatectomy. To date, the role of androgen deprivation therapy has not been formally shown. In this follow-up study, we aimed to update the results of the GETUG-AFU 16 trial, which assessed the efficacy of radiotherapy plus androgen suppression versus radiotherapy alone. Methods: GETUG-AFU 16 was an open-label, multicentre, phase 3, randomised, controlled trial that enrolled men (aged ≥18 years) with Eastern Cooperative Oncology Group performance status of 0 or 1, with histologically confirmed adenocarcinoma of the prostate (but no previous androgen suppression or pelvic radiotherapy), stage pT2, T3, or T4a (bladder neck involvement only) and pN0 or pNx according to the tumour, node, metastasis (TNM) staging system, whose prostate-specific antigen (PSA) concentration increased from 0·1 ng/mL to between 0·2 ng/mL and 2·0 ng/mL after radical prostatectomy, without evidence of clinical disease. Patients were assigned through central randomisation (1:1) to short-term androgen suppression (subcutaneous injection of 10·8 mg goserelin on the first day of irradiation and 3 months later) plus radiotherapy (3D conformal radiotherapy or intensity modulated radiotherapy of 66 Gy in 33 fractions, 5 days a week for 7 weeks) or radiotherapy alone. Randomisation was stratified using a permuted block method (block sizes of two and four) according to investigational site, radiotherapy modality, and prognosis. The primary endpoint was progression-free survival in the intention-to-treat population. This post-hoc one-shot data collection done 4 years after last data cutoff included patients who were alive at the time of the primary analysis and updated long-term patient status by including dates for first local progression, metastatic disease diagnosis, or death (if any of these had occurred) or the date of the last tumour evaluation or last PSA measurement. Survival at 120 months was reported. Late serious adverse effects were assessed. This trial is registered on ClinicalTrials.gov, NCT00423475 . Findings: Between Oct 19, 2006, and March 30, 2010, 743 patients were randomly assigned, 374 to radiotherapy alone and 369 to radiotherapy plus goserelin. At the time of data cutoff (March 12, 2019), the median follow-up was 112 months (IQR 102–123). The 120-month progression-free survival was 64% (95% CI 58–69) for patients treated with radiotherapy plus goserelin and 49% (43–54) for patients treated with radiotherapy alone (hazard ratio 0·54, 0·43–0·68; stratified log-rank test p<0·0001). Two cases of secondary cancer occurred since the primary analysis, but were not considered to be treatment related. No treatment-related deaths occurred. Interpretation: The 120-month progression-free survival confirmed the results from the primary analysis. Salvage radiotherapy combined with short-term androgen suppression significantly reduced risk of biochemical or clinical progression and death compared with salvage radiotherapy alone. The results of the GETUG-AFU 16 trial confirm the efficacy of androgen suppression plus radiotherapy as salvage treatment in patients with increasing PSA concentration after radical prostatectomy for prostate cancer. Funding: The French Health ministry, AstraZeneca, la Ligue Contre le Cancer, and La Ligue de Haute-Savoie.